Method for increasing density of high refractive index nanoimprint lithography film

By depositing metal oxides in the substrate nanoimprint film and the gaps therebetween, and using ALD technology to form a high-density optically densified nanoimprint film, the shortcomings of existing nanoimprint materials in terms of optical and mechanical properties are solved, and the effects of high refractive index, high hardness and low modulus are achieved.

JP2025060588AInactive Publication Date: 2025-04-10APPLIED MATERIALS INC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024197895
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-12-29
Filing Date
2024-11-13
Publication Date
2025-04-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing nanoimprint materials have shortcomings in terms of optical properties, mechanical properties and cost-effectiveness, especially the problems of low refractive index, low hardness and high modulus.

Method used

A high-density nanoimprint film based on substrate nanoimprint film and metal oxide is used to deposit metal oxides at the nanoimprint film and spaces between them through atomic layer deposition (ALD) technology to form an optically densified nanoimprint film with high refractive index, high hardness and low modulus.

Benefits of technology

The refractive index, hardness, destructivity and etch resistance of nanoimprint films are significantly improved, while reducing modulus, improving optical and mechanical properties, and improving cost-effectiveness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025060588000001_ABST
    Figure 2025060588000001_ABST
Patent Text Reader

Abstract

To provide densified nanoimprint films and processes for making these densified nanoimprint films, and optical devices.SOLUTION: A densified nanoimprint film 116 contains nanoparticles 108, a base nanoimprint film, and a metal oxide 112 disposed on the base nanoimprint film and in between the nanoparticles. The nanoparticles contain titanium oxide, zirconium oxide, niobium oxide, tantalum oxide, hafnium oxide, chromium oxide, indium tin oxide, silicon nitride, or any combination thereof. The metal oxide contains aluminum oxide, titanium oxide, zirconium oxide, niobium oxide, tantalum oxide, indium oxide, indium tin oxide, hafnium oxide, chromium oxide, scandium oxide, tin oxide, zinc oxide, yttrium oxide, praseodymium oxide, magnesium oxide, silicon oxide, silicon nitride, silicon oxynitride, or any combination thereof.SELECTED DRAWING: Figure 2A-2B
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] Field FIELD OF THE DISCLOSURE

[0001] Embodiments of the present disclosure relate generally to microdevice processing, and more specifically to nanoimprint lithography (NIL) films and processes for making the same. [Background technology]

[0002] Nano- and micro-patterning of nanoparticle imprinting provides an opportunity for developing nanomaterial-based optical systems, electronics, displays, energy devices, sensors, and other types of devices with nanometer-scale resolution. Currently available imprinting materials contain organic (high refractive index polymers) or inorganic-organic hybrid materials (sol-gel). Most of the imprinting materials have a low refractive index (<1.7) and have several problems related to optical transparency in the visible range, optical resolution, processability, high shrinkage of imprinted features, and cost-effectiveness. In addition, many of the imprinting materials have relatively low hardness, fracture strain, yield strength, and / or etch resistance, which would be advantageous to increase. Some imprinting materials have a relatively high elastic modulus, which would be advantageous to decrease.

[0003]

[0003] Therefore, there is a need for improved nanoimprinted films that have advantageous physical properties and associated processes for making these nanoimprinted films. Summary of the Invention

[0004]

[0004] The embodiments of the present disclosure generally relate to densified nanoimprint films and related processes for making such densified nanoimprint films. Densified nanoimprint films are also typically optically densified nanoimprint films compared to the base nanoimprint film or porous nanoimprint film from which they are formed. Densified nanoimprint films can be useful as nanoimprint lithography (NIL) films. Densified nanoimprint films and / or optically densified nanoimprint films typically have a relatively high refractive index (>1.9 or >2), as well as a relatively high hardness, fracture strain, yield strength, and / or etch resistance (e.g., reduced etch rate), and a relatively low modulus of elasticity.

[0005]

[0005] In one or more embodiments, the densified nanoimprint film includes a base nanoimprint film and a metal oxide disposed on the base nanoimprint film and between the nanoparticles. The base nanoimprint film includes nanoparticles, the nanoparticles including titanium oxide, zirconium oxide, niobium oxide, tantalum oxide, hafnium oxide, chromium oxide, indium tin oxide, silicon nitride, or any combination thereof. The metal oxide includes aluminum oxide, titanium oxide, zirconium oxide, niobium oxide, tantalum oxide, indium oxide, indium tin oxide, hafnium oxide, chromium oxide, scandium oxide, tin oxide, zinc oxide, yttrium oxide, praseodymium oxide, magnesium oxide, silicon oxide, silicon nitride, silicon oxynitride, or any combination thereof.

[0006]

[0006] In some embodiments, a method of forming a nanoimprinted film includes positioning a substrate containing a porous nanoimprinted film in a processing chamber, where the porous nanoimprinted film includes nanoparticles and voids between the nanoparticles, and depositing a metal oxide on the porous nanoimprinted film and within at least a portion of the voids to produce a densified nanoimprinted film during an atomic layer deposition (ALD) process.

[0007] In another embodiment, an optical device with a grating is provided that contains a densified nanoimprinted film as described herein. Any of the densified nanoimprinted films and / or methods for making densified nanoimprinted films as described and illustrated herein may be used to make an optical device. For example, the densified nanoimprinted film contains a base nanoimprinted film and a metal oxide disposed on and between the nanoparticles of the base nanoimprinted film as described and illustrated herein. [Brief description of the drawings]

[0008]

[0008] So that the above features of the present disclosure can be understood in detail, a specific description of the present disclosure briefly summarized above will be obtained by reference to embodiments, some of which are illustrated in the accompanying drawings. It should be noted, however, that the accompanying drawings illustrate only exemplary embodiments and therefore should not be considered as limiting the scope thereof, as other equally effective embodiments may be permitted.

[0009] [Figure 1A]

[0009] A cross-sectional view of a workpiece being processed through multiple operations during the preparation of a nanoimprinted film containing nanoparticles according to one or more embodiments described and illustrated herein. [Figure 1B]1A-1D are cross-sectional views of a work piece being processed through multiple operations during the preparation of a nanoimprinted film containing nanoparticles according to one or more embodiments described and illustrated herein. [Figure 1C] 1A-1D are cross-sectional views of a work piece being processed through multiple operations during the preparation of a nanoimprinted film containing nanoparticles according to one or more embodiments described and illustrated herein. [Figure 1D] 1A-1D are cross-sectional views of a work piece being processed through multiple operations during the preparation of a nanoimprinted film containing nanoparticles according to one or more embodiments described and illustrated herein. [Figure 1E] 1A-1D are cross-sectional views of a work piece being processed through multiple operations during the preparation of a nanoimprinted film containing nanoparticles according to one or more embodiments described and illustrated herein. [Figure 1F] 1A-1D are cross-sectional views of a work piece being processed through multiple operations during the preparation of a nanoimprinted film containing nanoparticles according to one or more embodiments described and illustrated herein. [Figure 2A-2B]

[0010] 1A-B are cross-sectional views of a workpiece being processed to prepare an optically densified nanoimprinted film according to one or more embodiments described and illustrated herein. [Diagram 3]

[0011] FIG. 2 is a front view of an optical device according to one or more embodiments described and illustrated herein.

[0010]

[0012] To facilitate understanding, wherever possible, identical reference numerals have been used to designate identical elements common to the figures. It is envisioned that elements and features of one or more embodiments may be beneficially incorporated in other embodiments. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011]

[0013] In one or more embodiments, a method of forming a nanoimprinted film includes positioning a substrate containing a base nanoimprinted film or a porous nanoimprinted film in a processing chamber, where the porous nanoimprinted film contains nanoparticles and voids between the nanoparticles, where the porous nanoimprinted film has a refractive index of less than 2. The voids, such as the spaces disposed between the nanoparticles, can contain ambient air, residual organic material (e.g., one or more hydrocarbons and / or other organic compounds), particulates, and / or one or more other contaminant materials, which can have a relatively low refractive index, such as about 1, about 1.2, or about 1.3 to about 1.4 or about 1.5.

[0012]

[0014] The method also includes depositing one or more metal oxides on the porous nanoimprint film and into at least a portion of the voids during an atomic layer deposition (ALD) process to produce an optically densified nanoimprint film. The voids can be at least partially filled, substantially filled, or completely filled. For example, at least 3%, at least 5%, or at least 10% of the volume occupied by the voids is filled with the metal oxide by the ALD process. In other examples, about 20% to about 90% of the volume occupied by the voids is filled with the metal oxide by the ALD process. In some examples, more than 90%, for example about 95% to 100%, of the volume occupied by the voids is filled with the metal oxide by the ALD process. The optically densified nanoimprint film has a refractive index higher than the refractive index of the base nanoimprint film or the porous nanoimprint film.

[0013]

[0015] In one or more embodiments, the refractive index of the optically densified nanoimprint film is about 0.5%, about 0.75%, about 1%, about 2%, about 4%, or about 5% to about 6%, about 8%, about 10%, about 12%, about 15%, about 20%, about 25%, about 30%, or more than the refractive index of the porous nanoimprint film. For example, the refractive index of the optically densified nanoimprint film is about 0.5% to about 30% higher than the refractive index of the porous nanoimprint film. In other examples, the refractive index of the optically densified nanoimprint film is about 0.65% to about 20% higher than the refractive index of the porous nanoimprint film. In other examples, the refractive index of the optically densified nanoimprint film is about 0.75% to about 10% higher than the refractive index of the porous nanoimprint film. In some embodiments, the refractive index of the optically densified nanoimprinted film is about 1% to about 6% higher than the refractive index of the porous nanoimprinted film.

[0014]

[0016] The refractive index of the porous nanoimprint film is about 1.50, about 1.65, or about 1.75 to about 1.80, about 1.85, about 1.90, about 1.95, about 1.97, about 1.99, or less than 2. In one or more embodiments, the refractive index of the porous nanoimprint film is about 1.5 to about 1.95 or about 1.75 to about 1.95. The refractive index of the optically densified nanoimprint film is higher than the refractive index of the porous nanoimprint film. In some embodiments, the refractive index of the optically densified nanoimprint film is about 1.8 or greater. For example, the refractive index of the optically densified nanoimprint film is about 1.8 to about 2.2, about 1.85 to about 2.15, or about 1.9 to about 2.1.

[0015]

[0017] Any of the densified nanoimprint films and / or optically densified nanoimprint films can have an increased mass per unit volume and / or a higher refractive index than the porous nanoimprint film and / or the base nanoimprint film, as described and discussed herein. In one or more embodiments, the densified nanoimprint film has a higher hardness, a higher strain at break, a higher yield strength, and / or a higher etch resistance than the porous nanoimprint film or the base nanoimprint film. In some embodiments, the densified nanoimprint film has a lower modulus of elasticity than the porous nanoimprint film or the base nanoimprint film.

[0016]

[0018] In one or more embodiments, the nanoparticles can be or include titanium oxide, zirconium oxide, niobium oxide, tantalum oxide, hafnium oxide, chromium oxide, indium tin oxide, silicon nitride, or any combination thereof. Any of the nanoparticles described and illustrated herein can be used to prepare a porous nanoimprint film. The metal oxide can be or include one or more of aluminum oxide, titanium oxide, zirconium oxide, niobium oxide, tantalum oxide, indium oxide, indium tin oxide, hafnium oxide, chromium oxide, scandium oxide, tin oxide, zinc oxide, yttrium oxide, praseodymium oxide, magnesium oxide, or any combination thereof. Instead of or together with the metal oxide, one or more silicon oxides and / or silicon nitrides can be deposited on and / or in the porous nanoimprint film. Exemplary silicon oxides include silicon monoxide, silicon dioxide, SiO xThe metal oxide may be or may include one or more silicon oxides, one or more silicates, silicon nitride, silicon oxynitride, or any combination thereof, where (2>x>1). The metal oxide may have a refractive index higher than, equal to, or lower than the refractive index of the nanoparticles and / or the porous nanoimprinted film. Even if the refractive index of the metal oxide is equal to or lower than the refractive index of the nanoparticles and / or the porous nanoimprinted film, the metal oxide has a higher refractive index than the material or materials replaced in the voids, such as air, organic compounds, particulates, and / or one or more other contaminant materials.

[0017] Method for preparing the imprint surface of a base nanoimprint film or a porous nanoimprint film

[0019] In one or more embodiments, a method for preparing an imprint surface, such as a nanoimprint lithography (NIL) film, is provided. The imprint surface is one or more exposed surfaces of a base nanoimprint film or a porous nanoimprint film as described and illustrated herein. The method includes disposing, coating, or otherwise placing an imprint composition on one or more substrates, contacting the imprint composition with a stamp having a pattern, converting the imprint composition into an imprint material (e.g., a porous nanoimprint film), and removing the stamp from the imprint material. In some examples, the substrate (e.g., a wafer) can be or include glass, quartz, silicon oxide, such as a glass substrate or a glass wafer. In other examples, the substrate can be or include silicon, silicon-germanium, plastic, and / or other materials. The imprint composition and / or material can have a refractive index of about 1.7 to about 2.0, or about 1.7 to less than 2, such as about 1.9, 1.85, or 1.80. The pattern on the stamp that is transferred to the imprint surface can be a one-dimensional pattern, a two-dimensional pattern, or a three-dimensional pattern.

[0018]

[0020] 1A-F are cross-sectional views of a workpiece that is processed through multiple operations during preparation of a nanoparticle-containing nanoimprint film, such as a base nanoimprint film or a porous nanoimprint film, according to one or more embodiments described and illustrated herein. The porous nanoimprint film is formed on a substrate by an imprint process. The imprint process includes disposing a nanoparticle-containing imprint composition 104 on a substrate 102 and aligning a stamp 120 on or adjacent to the imprint composition 104 (FIG. 1A). The imprint composition 104 is imprinted or otherwise contacted with the stamp 120 having a pattern (FIGS. 1B-1C). The imprint composition 104 is converted into a porous nanoimprint film 106 (FIG. 1D). In some examples, a thermal and / or radiation (UV light) curing process is used to convert the imprint composition 104 into a porous nanoimprint film 106. The stamp 120 is removed from the porous nanoimprinted film 106 (FIGS. 1E-1F) while still in place on the substrate 102. The pores of the porous nanoimprinted film 106 may have some residual organic material, such as minimal organic matrix present due to incomplete filling of the nanoparticles.

[0019]

[0021] In some embodiments, the imprint composition is disposed on the substrate by spin coating, drop casting, blade coating, and / or other coating processes. The imprint composition is disposed on the substrate as a film or layer having a predetermined thickness. The thickness of the imprint composition is about 50 nm, about 80 nm, about 100 nm, about 120 nm, about 150 nm, or about 200 nm to about 250 nm, about 300 nm, about 400 nm, about 500 nm, about 600 nm, about 800 nm, about 1000 nm, about 1200 nm, or more. For example, the thickness of the imprint composition is from about 50 nm to about 1000 nm, from about 100 nm to about 1000 nm, from about 200 nm to about 1000 nm, from about 400 nm to about 1000 nm, from about 500 nm to about 1,000 nm, from about 600 nm to about 1,000 nm, from about 800 nm to about 1,000 nm, from about 50 nm to about 600 nm, from about 100 nm to about 600 nm, from about 200 nm to about 600 nm, from about 400 nm to about 600 nm, from about 500 nm to about 600 nm, from about 50 nm to about 400 nm, from about 100 nm to about 400 nm, from about 200 nm to about 400 nm, or from about 300 nm to about 400 nm.

[0020]

[0022] The imprint composition is converted to an imprint material (e.g., a porous nanoimprint film) by exposing the imprint composition to heat, ultraviolet light, infrared light, visible light, microwave radiation, and / or any combination thereof. In one or more embodiments, when converting the imprint composition to an imprint material, the imprint composition is exposed to a light source having a wavelength of about 300 nm to about 365 nm. In other embodiments, when converting the imprint composition to an imprint material, the imprint composition is exposed to heat and maintained at a temperature of about 30° C. to about 100° C. for a period of about 30 seconds to about 1 hour. In some embodiments, the imprint composition is exposed to heat and maintained at a temperature of about 50° C. to about 60° C. for a period of about 1 minute to about 15 minutes.

[0021] ALD of Metal Oxides to Prepare Optically Densified Nanoimprinted Films

[0023] In one or more embodiments, one or more metal oxides are deposited or otherwise formed on and within the base nanoimprint film or the porous nanoimprint film by ALD or another vapor deposition process. The voids or portions of the voids within the porous nanoimprint film are at least partially filled with the metal oxide to produce an optically densified nanoimprint film. As described above, the voids can be at least partially filled, substantially filled, or completely filled with the metal oxide during the ALD process.

[0022] ALD of Metal Oxides to Prepare Optically Densified Nanoimprinted Films

[0024] 2A-B are cross-sectional views of a workpiece being processed to convert a porous nanoimprinted film into an optically densified nanoimprinted film according to one or more embodiments described and illustrated herein. The porous nanoimprinted film 106 including features 130 remains disposed on the substrate 102 as shown in FIG. 2A. The porous nanoimprinted film 106 contains a plurality of nanoparticles 108 separated by a plurality of spaces or voids 110. As shown in FIG. 2B, an ALD process or another vapor deposition process is used to deposit metal oxide 112 between the nanoparticles 108 and into the voids 110 to produce the optically densified nanoimprinted film 116. The features 130 formed in the porous nanoimprinted film 106 are at least substantially, if not completely, preserved in the optically densified nanoimprinted film 116.

[0023]

[0025] The ALD process includes sequentially exposing the porous nanoimprinted film to a metal precursor and an oxidizer (and / or other reagents) during an ALD cycle to deposit a metal oxide. The ALD cycle also includes exposure of a purge gas between each exposure of the precursor. For example, the ALD process includes sequentially exposing the porous nanoimprinted film to a metal precursor, a purge gas, an oxidizer (and / or other reagents), and a purge gas during an ALD cycle. The purge gas can be nitrogen (N 2 ), argon, helium, or any combination thereof.

[0024]

[0026] In some examples, one ALD cycle can be performed to deposit a metal oxide during the generation of an optically densified nanoimprinted film. In other examples, two or more ALD cycles can be performed to deposit a metal oxide during the generation of an optically densified nanoimprinted film. For example, an ALD cycle can be repeated from 2, 3, 4, 5, 6, 7, 8, 9, 10, 12, or 15 times to about 18, about 20, about 25, about 30, about 40, about 50, about 60, about 80, about 100 times, or more times to deposit a metal oxide during the generation of an optically densified nanoimprinted film.

[0025]

[0027] In one or more embodiments, when the metal oxide is or contains aluminum oxide, the metal precursor is one or more aluminum precursors, such as alkylaluminum compounds, for example, trimethylaluminum, triethylaluminum, tripropylaluminum, or tributylaluminum. The oxidizing agent can be water, oxygen (O 2 ), ozone, atomic oxygen, nitrous oxide, hydrogen peroxide, one or more organic peroxides, plasmas thereof, or any combination thereof.

[0026]

[0028] In one or more embodiments, the optically densified nanoimprint film contains a base nanoimprint film having nanoparticles and optionally voids between the nanoparticles, the base nanoimprint film having a refractive index less than 2. The optically densified nanoimprint film also contains a metal oxide disposed on the base nanoimprint film and contained within at least a portion of the voids. The optically densified nanoimprint film has a refractive index higher than that of the base nanoimprint film.

[0027] Imprint Composition for Preparing NIL Films

[0029] FIELD OF THE DISCLOSURE Embodiments of the present disclosure generally relate to imprint compositions and imprint materials (e.g., base nanoimprint films or porous nanoimprint films) useful for nanoimprint lithography (NIL). The imprint composition can be converted to an imprint material by application of heat and / or one or more types of radiation, such as light or microwave. In one or more embodiments, the imprint composition contains one or more types of nanoparticles, one or more surface ligands, one or more solvents, one or more additives, and one or more acrylates.

[0028]

[0030] Each of the nanoparticles may be a single particle (bare particle) or a coated particle, for example, containing a core and one or more shells disposed around the core. In some examples, the nanoparticles may contain one or more types of surface ligands (e.g., tethered NPs or stabilized NPs) attached to the outer surface of the particle. The nanoparticles may have one or more different shapes or geometries, such as spherical, ellipsoidal, rod-like, cubic, wire, cylindrical, rectangular, or combinations thereof.

[0029]

[0031] The nanoparticles or cores can have a size or diameter of about 2 nm, about 5 nm, about 8 nm, about 10 nm, about 12 nm, about 15 nm, about 20 nm, about 25 nm, about 30 nm, or about 35 nm to about 40 nm, about 50 nm, about 60 nm, about 80 nm, about 100 nm, about 150 nm, about 200 nm, about 250 nm, about 300 nm, about 400 nm, about 500 nm, or greater. For example, the nanoparticles or cores may be from about 2 nm to about 500 nm, from about 2 nm to about 300 nm, from about 2 nm to about 200 nm, from about 2 nm to about 150 nm, from about 2 nm to about 100 nm, from about 2 nm to about 80 nm, from about 2 nm to about 60 nm, from about 2 nm to about 50 nm, from about 2 nm to about 40 nm, from about 2 nm to about 30 nm, from about 2 nm to about 20 nm, from about 2 nm to about 15 nm, from about 2 nm to about 10 nm, from about 10 nm to about 500 nm, from about 10 nm to about 300 nm, from about 10 nm to about 200 nm, from about 10 nm to about 1 It can have a size or diameter of 50 nm, about 10 nm to about 100 nm, about 10 nm to about 80 nm, about 10 nm to about 60 nm, about 10 nm to about 50 nm, about 10 nm to about 40 nm, about 10 nm to about 30 nm, about 10 nm to about 20 nm, about 10 nm to about 15 nm, about 50 nm to about 500 nm, about 50 nm to about 300 nm, about 50 nm to about 200 nm, about 50 nm to about 150 nm, about 50 nm to about 100 nm, about 50 nm to about 80 nm, or about 50 nm to about 60 nm.

[0030]

[0032] The nanoparticles can be or contain one or more metal oxides, one or more non-metal oxides, one or more non-metal nitrides, and / or diamond materials. The nanoparticles can contain titanium oxide, zirconium oxide, niobium oxide, tantalum oxide, hafnium oxide, chromium oxide, indium tin oxide, silicon nitride, diamond, or any combination thereof. In some embodiments, when the nanoparticles contain one or more shells disposed around the core, the core and shell can be the same material or different materials. In one or more examples, the core contains titanium oxide and the shell contains silicon oxide, zirconium oxide, niobium oxide, or any combination thereof. In other examples, the core contains niobium oxide and the shell contains silicon oxide, zirconium oxide, or any combination thereof. In some examples, the core contains zirconium oxide and the shell contains silicon oxide.

[0031]

[0033] In some embodiments, the core has a diameter of about 2 nm to about 500 nm and the shell has a thickness of about 0.1 nm to about 100 nm. In other embodiments, the core has a diameter of about 5 nm to about 200 nm and the shell has a thickness of about 0.5 nm to about 60 nm. In some embodiments, the core has a diameter of about 10 nm to about 100 nm and the shell has a thickness of about 1 nm to about 15 nm.

[0032]

[0034] In one or more embodiments, the imprint composition contains about 0.1%, about 0.5%, about 1%, about 2%, about 3%, about 5%, about 6%, about 8%, or about 10% to about 12%, about 15%, about 18%, about 20%, about 22%, about 24%, about 25%, about 28%, about 30%, about 32%, about 35%, about 38%, or about 40% by weight of nanoparticles. For example, the imprint composition may comprise from about 0.1% to about 40% by weight, from about 0.5% to about 40% by weight, from about 0.5% to about 35% by weight, from about 0.5% to about 32% by weight, from about 0.5% to about 30% by weight, from about 0.5% to about 28% by weight, from about 0.5% to about 25% by weight, from about 0.5% to about 22% by weight, from about 0.5% to about 20% by weight, from about 0.5% to about 18% by weight, from about 0.5% to about 15 ...28% by weight, from about 0.5% to about 25% by weight, from about 0.5% to about 22% by weight, from about 0.5% to about 20% by weight, from about 0.5% to about 28% by weight, from about 0.5% to about 25% by weight, from about 0.5% to about 22% by weight, from about 0.5% to about 20% by weight, from about 0.5% to about 28% by weight, from about 0.5% to about 25% by weight, from about 0.5 % to about 12% by weight, about 0.5% to about 10% by weight, about 0.5% to about 8% by weight, about 0.5% to about 6% by weight, about 0.5% to about 5% by weight, 0.5% to about 4% by weight, about 0.5% to about 3% by weight, about 0.5% to about 2% by weight, about 0.5% to about 1.5% by weight, about 0.5% to about 1% by weight, about 2% to about 40% by weight, about 2% to about 35% by weight, about 2% to about 32% by weight, about 2% by weight to about 30% by weight, about 2% to about 28% by weight, about 2% to about 25% by weight, about 2% to about 22% by weight, about 2% to about 20% by weight, about 2% to about 18% by weight, about 2% to about 15% by weight, about 2% to about 12% by weight, about 2% to about 10% by weight, about 2% to about 8% by weight, about 2% to about 6% by weight, about 2% to about 5% by weight, about 2% to about 4% by weight, about 2% to about 3% by weight, about 5% to about 40% by weight %, about 5% to about 35% by weight, about 5% to about 32% by weight, about 5% to about 30% by weight, about 5% to about 28% by weight, about 5% to about 25% by weight, about 5% to about 22% by weight, about 5% to about 20% by weight, about 5% to about 18% by weight, about 5% to about 15% by weight, about 5% to about 12% by weight, about 5% to about 10% by weight, about 5% to about 8% by weight, or about 5% to about 6% by weight of nanoparticles.

[0033]

[0035] In other embodiments, the imprint composition contains about 40%, about 50%, about 55%, about 60%, about 62%, or about 65% to about 68%, about 70%, about 75%, about 80%, about 85%, about 88%, about 90%, about 92%, about 93%, about 94%, about 95%, about 96%, about 97%, about 98% or more nanoparticles by weight. For example, the imprint composition contains about 40% to about 98% by weight, about 50% to about 95% by weight, about 50% to about 90% by weight, about 50% to about 80% by weight, about 50% to about 75% by weight, about 50% to about 70% by weight, about 50% to about 65% by weight, about 50% to about 60% by weight, about 50% to about 55% by weight, about 60% to about 95% by weight, about 60% to about 90% by weight, about 60% to about 80% by weight, about 60% to about 75% by weight, about 60% to about 70% by weight, about 60% to about 65% by weight, about 70% to about 95% by weight, about 70% to about 90% by weight, about 70% to about 80% by weight, or about 70% to about 75% by weight of nanoparticles.

[0034]

[0036] The surface ligands can be or include one or more carboxylic acids, one or more esters, one or more amines, one or more alcohols, one or more silanes, salts thereof, complexes thereof, or any combination thereof. Exemplary surface ligands can be or include oleic acid, stearic acid, propionic acid, benzoic acid, palmitic acid, myristic acid, methylamine, oleylamine, butylamine, benzyl alcohol, oleyl alcohol, butanol, octanol, dodecanol, octeyltriethoxysilane, octeyltrimethoxysilane, 3-(trimethoxysilyl)propyl methacrylate, propyltriethoxysilane, salts thereof, esters thereof, complexes thereof, or any combination thereof. In some examples, the surface ligands are at a concentration of about 8% to about 50% by weight based on the weight of the nanoparticles.

[0035]

[0037] The imprint composition contains about 0.5%, about 1%, about 2%, about 3%, about 5%, about 7%, about 8%, or about 10% to about 12%, about 15%, about 18%, about 20%, about 25%, about 30%, about 35%, about 40%, about 45%, or about 50% by weight of surface ligands. For example, the imprint composition can be from about 0.5% to about 50% by weight, from about 1% to about 50% by weight, from about 3% to about 50% by weight, from about 5% to about 50% by weight, from about 5% to about 40% by weight, from about 5% to about 35% by weight, from about 5% to about 30% by weight, from about 5% to about 25% by weight, from about 5% to about 20% by weight, from about 5% to about 15% by weight, from about 5% to about 10% by weight, from about 10% to about 50% by weight, from about 10% to about 50% by weight, In some embodiments, the surface ligand comprises from about 10% to about 40%, from about 10% to about 35%, from about 10% to about 30%, from about 10% to about 25%, from about 10% to about 20%, from about 10% to about 15%, from about 15% to about 50%, from about 15% to about 40%, from about 15% to about 35%, from about 15% to about 30%, from about 15% to about 25%, or from about 15% to about 20% by weight of the surface ligand.

[0036]

[0038] The solvent can be or include one or more nanoparticle dispersion solvents, one or more imprinting solvents, other types of solvents, or any combination thereof. The nanoparticle dispersion solvent can be or include one or more glycol ethers, alcohols, acetates, esters thereof, salts thereof, derivatives thereof, or any combination thereof. In some examples, the nanoparticle dispersion solvent can be or include one or more p-series glycol ethers, one or more e-series glycol ethers, or any combination thereof. In one or more examples, the nanoparticle dispersion solvent contains propylene glycol methyl ether acetate (PGMEA). The imprinting solvent can be or include one or more alcohols, one or more esters, salts thereof, or any combination thereof. In one or more examples, the imprinting solvent contains ethyl lactate.

[0037]

[0039] In one or more embodiments, the imprint composition contains about 50%, about 55%, about 60%, about 62%, about 65%, about 68%, about 70%, about 72%, about 75%, or about 80% to about 83%, about 85%, about 87%, about 88%, about 90%, about 92%, about 94%, about 95%, about 97%, or about 98% by weight of one or more solvents. For example, the imprint composition may comprise from about 50% to about 98% by weight, from about 60% to about 98% by weight, from about 60% to about 95% by weight, from about 60% to about 90% by weight, from about 60% to about 88% by weight, from about 60% to about 85% by weight, from about 60% to about 83% by weight, from about 60% to about 80% by weight, from about 60% to about 78% by weight, from about 60% to about 75% by weight, from about 60% to about 72% by weight, from about 60% to about 70% by weight, from about 60% to about 68% by weight, from about 60% to about 65% by weight, from about 60% to about 63% by weight, from about 70% to about 98% by weight, about 70% to about 95% by weight, about 70% to about 90% by weight, about 70% to about 88% by weight, about 70% to about 85% by weight, about 70% to about 83% by weight, about 70% to about 80% by weight, about 70% to about 78% by weight, about 70% to about 75% by weight, about 70% to about 72% by weight, about 80% to about 98% by weight, about 80% to about 95% by weight, about 80% to about 90% by weight, about 80% to about 88% by weight, about 80% to about 85% by weight, about 80% to about 83% by weight, or about 80% to about 82% by weight of one or more solvents.

[0038]

[0040] In some embodiments, the imprint composition contains about 0.5%, about 0.8%, about 1%, about 1.5%, about 2%, about 2.5%, about 3%, about 3.5%, about 4%, about 5%, or about 6% to about 7%, about 8%, about 10%, about 12%, about 14%, about 15%, about 18%, about 20%, or about 25% by weight of nanoparticle dispersion solvent. For example, the imprint composition may comprise from about 0.5% to about 20% by weight, from about 1% to about 20% by weight, from about 1% to about 18% by weight, from about 1% to about 15% by weight, from about 1% to about 13% by weight, from about 1% to about 12% by weight, from about 1% to about 11% by weight, from about 1% to about 10% by weight, from about 1% to about 8% by weight, from about 1% to about 7% by weight, from about 1% to about 6% by weight, from about 1% to about 5% by weight, from about 1% to about 4% by weight, from about 1% to about 3% by weight, from about 5% to about 20% by weight, from about 5% to about 18% by weight, The nanoparticle dispersion solvent may comprise about 5% to about 15% by weight, about 5% to about 13% by weight, about 5% to about 12% by weight, about 5% to about 11% by weight, about 5% to about 10% by weight, about 5% to about 8% by weight, about 5% to about 7% by weight, about 5% to about 6% by weight, about 8% to about 20% by weight, about 8% to about 18% by weight, about 8% to about 15% by weight, about 8% to about 13% by weight, about 8% to about 12% by weight, about 8% to about 11% by weight, about 8% to about 10% by weight, or about 8% to about 9% by weight.

[0039]

[0041] In other embodiments, the imprinting composition contains about 50, 55, 60, 62, 65, 68, or 70% to about 72, 75, 78, 80, 82, 83, 85, 87, 88, 90, or 95% by weight of the imprinting solvent. For example, the imprint composition may comprise from about 50% to about 95% by weight, from about 60% to about 95% by weight, from about 60% to about 90% by weight, from about 60% to about 88% by weight, from about 60% to about 85% by weight, from about 60% to about 83% by weight, from about 60% to about 80% by weight, from about 60% to about 78% by weight, from about 60% to about 75% by weight, from about 60% to about 72% by weight, from about 60% to about 70% by weight, from about 60% to about 68% by weight, from about 60% to about 65% by weight, from about 60% to about 63% by weight, from about 70% to about 98% by weight, from about 70% to about 95 ... 0% to about 90% by weight, about 70% to about 88% by weight, about 70% to about 85% by weight, about 70% to about 83% by weight, about 70% to about 80% by weight, about 70% to about 78% by weight, about 70% to about 75% by weight, about 70% to about 72% by weight, about 75% to about 98% by weight, about 75% to about 95% by weight, about 75% to about 90% by weight, about 75% to about 88% by weight, about 75% to about 85% by weight, about 75% to about 83% by weight, about 75% to about 80% by weight, or about 75% to about 78% by weight of imprinting solvent.

[0040]

[0042] The additives can be or include one or more perfluoroalkyl ethers, one or more polyglycols, one or more fatty acids, one or more silanes, one or more siloxanes, or any combination thereof. Exemplary additives can be or include fluorosurfactants, fluoroadditives, and / or fluorocarbons (e.g., CAPSTONE® FS-66 or FS-68 fluorosurfactants available from DuPont), glycolic acid ethoxylate oleyl ether, polyethylene glycol, polypropylene glycol, lauric acid, myristic acid, stearic acid, palmitic acid, dimethyldiethoxysilane, polydimethylsiloxane, polydiphenylsiloxane, hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, silanol-terminated polydimethylsiloxane, vinyl-terminated polydimethylsiloxane, 1,2-propanediol, salts thereof, esters thereof, complexes thereof, or any combination thereof. The additive can be or can include one or more diols, one or more alcohols having three or more alcohol groups, or any combination thereof. In one or more embodiments, the additive includes 1,2-propanediol. In some embodiments, the additive is at a concentration of about 0.01% to about 2.5% by weight based on the weight of the nanoparticles.

[0041]

[0043] The imprint composition contains about 0.01%, about 0.05%, about 0.1%, about 0.2%, about 0.3%, about 0.5%, about 0.8%, or about 1% to about 1.2%, about 1.5%, about 1.8%, about 2%, about 2.5%, about 3%, about 3.5%, about 4%, about 5%, about 6%, about 8%, or about 10% by weight of the additive. For example, the imprint composition may be from about 0.01% to about 10% by weight, from about 0.01% to about 8% by weight, from about 0.01% to about 5% by weight, from about 0.01% to about 4% by weight, from about 0.01% to about 3% by weight, from about 0.01% to about 2% by weight, from about 0.01% to about 1% by weight, from about 0.01% to about 0.5% by weight, from about 0.01% to about 0.1% by weight, from about 0.01% to about 0.05% by weight, from about 0.1% to about 10 ... % to about 8% by weight, about 0.1% to about 5% by weight, about 0.1% to about 4% by weight, about 0.1% to about 3% by weight, about 0.1% to about 2% by weight, about 0.1% to about 1% by weight, about 0.1% to about 0.5% by weight, about 1% to about 10% by weight, about 1% to about 8% by weight, about 1% to about 5% by weight, about 1% to about 4% by weight, about 1% to about 3% by weight, about 1% to about 2% by weight, or about 1% to about 1.5% by weight of the additive.

[0042]

[0044] The acrylate can be or include one or more methacrylates, one or more ethyl acrylates, one or more propyl acrylates, one or more butyl acrylates, one or more monofunctional acrylates, one or more difunctional acrylates, one or more trifunctional acrylates, other multifunctional acrylates, or any combination thereof. Exemplary acrylates can be or include 3-(trimethoxysilyl)propyl methacrylate (3-MPS), 3-(trimethoxysilyl)propyl acrylate, di(ethylene glycol) methyl ether methacrylate, ethylene glycol methyl ether methacrylate, 2-ethylhexyl methacrylate, ethyl methacrylate, hexyl methacrylate, methacrylic acid, vinyl methacrylate, monomers thereof, polymers thereof, salts thereof, complexes thereof, or any combination thereof. In some examples, the acrylate is at a concentration of about 0.05% to about 10% by weight based on the weight of the nanoparticles.

[0043]

[0045] The imprint composition contains about 0.1%, about 0.2%, about 0.3%, about 0.5%, about 0.8%, about 1% to about 1.2%, about 1.5%, about 1.8%, or about 2%, about 2.2%, about 2.3%, about 2.5%, about 2.8%, about 3%, about 3.2%, about 3.5%, about 3.8%, about 4%, about 5%, about 6%, about 8%, about 10%, about 12%, about 15%, about 18%, or about 20% by weight of acrylate. For example, the imprint composition may comprise from about 0.1% to about 20% by weight, from about 0.1% to about 15% by weight, from about 0.1% to about 10% by weight, from about 0.1% to about 8% by weight, from about 0.1% to about 5% by weight, from about 0.1% to about 4% by weight, from about 0.1% to about 3% by weight, from about 0.1% to about 2% by weight, from about 0.1% to about 1% by weight, from about 0.1% to about 1% by weight, % to about 0.5% by weight, about 1% to about 20% by weight, about 1% to about 15% by weight, about 1% to about 10% by weight, about 1% to about 8% by weight, about 1% to about 5% by weight, about 1% to about 4% by weight, about 1% to about 3.5% by weight, about 1% to about 3.2% by weight, about 1% to about 3% by weight, about 1% to about 2.8% by weight, about 1% to about 2% by weight, about 1% to about 3.5% by weight, about 1% to about 3.2% by weight, about 1% to about 3% by weight, about 1% to about 2.8% by weight, about 1% to about 2.5% by weight, about 1% to about 3 ... 0.5% by weight, about 1% to about 2.3% by weight, about 1% to about 2.2% by weight, about 1% to about 2% by weight, about 1% to about 1.8% by weight, about 1% to about 1.5% by weight, about 1.8% to about 20% by weight, about 1.8% to about 15% by weight, about 1.8% to about 10% by weight, about 1.8% to about 8% by weight, about 1.8% to about 5% by weight, about 1.5% to about 20 ... 0.8% to about 4%, about 1.8% to about 3.5%, about 1.8% to about 3.2%, about 1.8% to about 3%, about 1.8% to about 2.8%, about 1.8% to about 2.5%, about 1.8% to about 2.3%, about 1.8% to about 2.2%, or about 1.8% to about 2% acrylate by weight.

[0044]

[0046] In one or more embodiments, the imprint composition contains about 0.5% to about 40% by weight nanoparticles, about 50% to about 90% by weight one or more solvents, about 5% to about 40% by weight surface ligands, about 0.01% to about 5% by weight additives, and about 0.1% to about 10% by weight acrylate. In other embodiments, the imprint composition contains about 1% to about 25% by weight nanoparticles, about 60% to about 85% by weight one or more solvents, about 6% to about 35% by weight surface ligands, about 0.05% to about 3% by weight additives, and about 0.3% to about 8% by weight acrylate. In some examples, the imprint composition contains about 5% to about 20% by weight of nanoparticles, about 65% to about 80% by weight of one or more solvents, about 7% to about 31% by weight of surface ligands, about 0.09% to about 1.5% by weight of additives, and about 0.5% to about 6% by weight of acrylate.

[0045]

[0047] The imprint composition can have a viscosity of about 1 cP, about 2 cP, about 3 cP, about 5 cP, about 8 cP, or about 10 cP to about 12 cP, about 15 cP, about 20 cP, about 25 cP, about 30 cP, about 40 cP, about 50 cP, or about 70 cP. For example, the imprint composition can have a viscosity of about 1 cP to about 70 cP, about 1 cP to about 50 cP, about 1 cP to about 40 cP, about 1 cP to about 30 cP, about 1 cP to about 20 cP, about 1 cP to about 10 cP, about 1 cP to about 5 cP, about 10 cP to about 70 cP, about 10 cP to about 50 cP, about 10 cP to about 40 cP, about 10 cP to about 30 cP, about 10 cP to about 20 cP, about 20 cP to about 70 cP, about 20 cP to about 50 cP, about 20 cP to about 40 cP, about 20 cP to about 30 cP, or about 20 cP to about 25 cP.

[0046]

[0048] In one or more embodiments, one or more acrylates in the imprint composition may polymerize and / or oligomerize during formation (e.g., curing or otherwise converting) of an imprint material, such as a porous nanoimprint film.

[0047]

[0049] Below are some theoretical examples of imprint compositions that can be produced by the embodiments described and illustrated herein. TIFF2025060588000002.tif76170TIFF2025060588000003.tif78170TIFF2025060588000004.tif76170

[0048]

[0050] FIG. 3 is a front view of an optical device 300 including the optically densified nanoimprint film 306 shown in FIG. 2B according to one or more embodiments described and illustrated herein. In any embodiment described herein, the optically densified nanoimprint film 116 shown in FIG. 2B can be the same as or used as the optically densified nanoimprint film 306 as shown in FIG. 3. It should be understood that the optical device 300 described below is an exemplary optical device. In one or more embodiments, the optical device 300 is a waveguide coupler, such as an augmented reality waveguide coupler. In other embodiments, the optical device 300 is a planar optical device, such as a metasurface. The optical device 300 includes a plurality of device structures 304. The device structures 304 may be nanostructures having nano-sized dimensions, such as sub-micron dimensions, e.g., critical dimensions less than 1 μm. In one or more embodiments, the regions of the device structures 304 correspond to one or more gratings 302, such as grating areas 302a and 302b. In one or more embodiments, the optical device 300 includes a first grating area 302a and a second grating area 302b, each of the first grating areas 302a and 302b including a plurality of device structures 304, respectively.

[0049]

[0051] The depth of the grating 302 may vary across the grating areas 302a and 302b in the embodiments described herein. In some embodiments, the depth of the grating 302 may vary smoothly across the first grating area 302a and across the second grating area 302b. In one or more examples, the depth may range from about 10 nm to about 400 nm across one of the grating areas. The grating area 302a may range from about 20 mm to about 50 mm on a given side in some examples. Thus, in some examples, the angle of change in the depth of the grating 302 may be on the order of 0.0005 degrees.

[0050]

[0052] In the embodiments described herein, the device structures 304 can be created using laser ablation. Laser ablation as used herein is used to create three-dimensional microstructures in the device material, or, optionally, to create variable depth structures in a sacrificial layer covering the device material as part of a variable depth structure process. Using laser ablation to create the optical structures 304 allows for fewer processing steps and higher variable depth resolution than existing methods.

[0051]

[0053] Embodiments of the present disclosure further relate to any one or more of paragraphs 1-68 below.

[0052]

[0054] 1. A method of forming a nanoimprinted film, the method comprising: positioning a substrate including a porous nanoimprinted film in a processing chamber, the porous nanoimprinted film including nanoparticles and voids between the nanoparticles, the porous nanoimprinted film having a refractive index of less than 2; and depositing a metal oxide on the porous nanoimprinted film and within at least a portion of the voids to produce an optically densified nanoimprinted film during an atomic layer deposition (ALD) process.

[0053]

[0055] 2. The method of paragraph 1, wherein the metal oxide has a refractive index higher than the refractive index of the porous nanoimprinted film.

[0054]

[0056] 3. The method of paragraph 1 or 2, wherein the metal oxide has a refractive index lower than the refractive index of the porous nanoimprinted film.

[0055]

[0057] 4. The method of any one of paragraphs 1-3, wherein the optically densified nanoimprinted film has a refractive index higher than the refractive index of the porous nanoimprinted film.

[0056]

[0058] 5. The method of paragraph 4, wherein the refractive index of the optically densified nanoimprinted film is about 0.5% to about 30% higher than the refractive index of the porous nanoimprinted film.

[0057]

[0059] 6. The method of paragraph 5, wherein the refractive index of the optically densified nanoimprinted film is about 0.75% to about 10% higher than the refractive index of the porous nanoimprinted film.

[0058]

[0060] 7. The method of paragraph 6, wherein the refractive index of the optically densified nanoimprinted film is about 1% to about 6% higher than the refractive index of the porous nanoimprinted film.

[0059]

[0061] 8. The method of any one of paragraphs 1 to 7, wherein the refractive index of the porous nanoimprinted film is from about 1.5 to about 1.95.

[0060]

[0062] 9. The method of any one of paragraphs 1 to 8, wherein the optically densified nanoimprinted film has a refractive index of about 1.8 or greater.

[0061]

[0063] 10. The method of any one of paragraphs 1-9, wherein the metal oxide comprises aluminum oxide, titanium oxide, zirconium oxide, niobium oxide, tantalum oxide, indium oxide, indium tin oxide, hafnium oxide, chromium oxide, scandium oxide, tin oxide, zinc oxide, yttrium oxide, praseodymium oxide, magnesium oxide, silicon oxide, silicon nitride, silicon oxynitride, or any combination thereof.

[0062]

[0064] 11. The method of any one of paragraphs 1-10, wherein the nanoparticles comprise titanium oxide, zirconium oxide, niobium oxide, tantalum oxide, hafnium oxide, chromium oxide, indium tin oxide, silicon nitride, or any combination thereof.

[0063]

[0065] 12. The method of any one of paragraphs 1-11, wherein the ALD process includes sequentially exposing the porous nanoimprinted film to a metal precursor and an oxidant during an ALD cycle to deposit a metal oxide.

[0064]

[0066] 13. The method of paragraph 12, wherein the ALD cycle is repeated from 1 to about 50 times during deposition of the metal oxide during the ALD process.

[0065]

[0067] 14. The method of any one of paragraphs 1-13, wherein at least 3% of the volume occupied by the voids is filled with metal oxide by an ALD process.

[0066]

[0068] 15. The method of any one of paragraphs 1-14, wherein about 20% to about 90% of the volume occupied by the voids is filled with metal oxide by an ALD process.

[0067]

[0069] 16. The method of any one of paragraphs 1-15, wherein a porous nanoimprinted film is formed on the substrate by an imprint process including disposing an imprint composition comprising nanoparticles on the substrate, contacting the imprint composition with a stamp having a pattern, converting the imprint composition into a porous nanoimprinted film, and removing the stamp from the porous nanoimprinted film.

[0068]

[0070] 17. The method of paragraph 16, wherein the imprint composition is converted into a porous nanoimprint film by exposing the imprint composition to heat, ultraviolet light, infrared light, visible light, microwave radiation, or any combination thereof.

[0069]

[0071] 18. The method of paragraph 16, wherein converting the imprint composition into a porous nanoimprint film further comprises exposing the imprint composition to a light source having a wavelength of about 300 nm to about 365 nm.

[0070]

[0072] 19. The method of paragraph 16, wherein converting the imprint composition into a porous nanoimprint film further comprises heating the imprint composition to a temperature of about 30° C. to about 100° C. for a period of about 30 seconds to about 1 hour.

[0071]

[0073] 20. The method of paragraph 16, wherein converting the imprint composition into a porous nanoimprint film further comprises heating the imprint composition to a temperature of about 50° C. to about 60° C. for a period of about 1 minute to about 15 minutes.

[0072]

[0074] 21. The method of paragraph 16, wherein the imprint composition is disposed on the substrate by spin coating, drop casting, or blade coating.

[0073]

[0075] 22. The method of paragraph 16, wherein the imprint composition is disposed on the substrate as a layer having a thickness of about 50 nm to about 1000 nm.

[0074]

[0076] 23. The method of paragraph 16, wherein the imprint composition is disposed on the substrate as a layer having a thickness of about 100 nm to about 400 nm.

[0075]

[0077] 24. The method of paragraph 16, wherein the pattern on the stamp is a one-dimensional pattern, a two-dimensional pattern, or a three-dimensional pattern.

[0076]

[0078] 25. A method of forming a nanoimprint film comprising: disposing an imprint composition comprising nanoparticles on a substrate; contacting the imprint composition with a stamp having a pattern; converting the imprint composition to a porous nanoimprint film; removing the stamp from the porous nanoimprint film; disposing the substrate comprising the porous nanoimprint film in a processing chamber, wherein the porous nanoimprint film comprises nanoparticles and voids between the nanoparticles, the porous nanoimprint film having a refractive index less than 2; and depositing a metal oxide on the porous nanoimprint film and in at least a portion of the voids to produce an optically densified nanoimprint film during an atomic layer deposition (ALD) process, wherein the optically densified nanoimprint film has a refractive index higher than that of the porous nanoimprint film.

[0077]

[0079] 26. An optically densified nanoimprint film comprising a base nanoimprint film comprising nanoparticles and voids between the nanoparticles, the base nanoimprint film having a refractive index less than 2; and an optically densified nanoimprint film comprising a metal oxide disposed on the base nanoimprint film and contained within at least a portion of the voids, the metal oxide having a refractive index higher than the refractive index of the base nanoimprint film.

[0078]

[0080] 27. The optically densified nanoimprint film of paragraph 26, wherein the refractive index of the optically densified nanoimprint film is about 0.5% to about 30% higher than the refractive index of the base nanoimprint film.

[0079]

[0081] 28. The optically densified nanoimprint film of paragraph 27, wherein the refractive index of the optically densified nanoimprint film is about 0.75% to about 10% higher than the refractive index of the base nanoimprint film.

[0080]

[0082] 29. The optically densified nanoimprint film of paragraph 28, wherein the refractive index of the optically densified nanoimprint film is about 1% to about 6% higher than the refractive index of the base nanoimprint film.

[0081]

[0083] 30. The optically densified nanoimprint film of any one of paragraphs 26-29, wherein the refractive index of the base nanoimprint film is from about 1.5 to about 1.95.

[0082]

[0084] 31. The optically densified nanoimprinted film of any one of paragraphs 26-30, wherein the refractive index of the optically densified nanoimprinted film is from about 1.8 to about 2.05.

[0083]

[0085] 32. The optically densified nanoimprint film of any one of paragraphs 26-31, wherein the metal oxide comprises aluminum oxide, titanium oxide, zirconium oxide, niobium oxide, tantalum oxide, indium oxide, indium tin oxide, hafnium oxide, chromium oxide, scandium oxide, tin oxide, zinc oxide, yttrium oxide, praseodymium oxide, magnesium oxide, silicon oxide, silicon nitride, silicon oxynitride, or any combination thereof.

[0084]

[0086] 33. The optically densified nanoimprinted film of any one of paragraphs 26-32, wherein the nanoparticles comprise titanium oxide, zirconium oxide, niobium oxide, tantalum oxide, hafnium oxide, chromium oxide, indium tin oxide, silicon nitride, or any combination thereof.

[0085]

[0087] 34. The optically densified nanoimprint film of any one of paragraphs 26-33, wherein at least 3% of the volume occupied by voids in the base nanoimprint film contains a metal oxide.

[0086]

[0088] 35. The optically densified nanoimprint film of any one of paragraphs 26-34, wherein about 20% to about 90% of the volume occupied by voids in the base nanoimprint film contains a metal oxide.

[0087]

[0089] 36. An optical device with a grating, comprising an optically densified nanoimprinted film produced by the method of any one of paragraphs 1-25.

[0088]

[0090] 37. An optical device comprising a grating, the optically densified nanoimprinted film comprising any one of paragraphs 26 to 35.

[0089]

[0091] 38. An optical device with a grating comprising an optically densified nanoimprint film, the optically densified nanoimprint film comprising a base nanoimprint film comprising nanoparticles and voids between the nanoparticles, the base nanoimprint film having a refractive index less than 2, and a metal oxide disposed on the base nanoimprint film and contained within at least a portion of the voids, the optically densified nanoimprint film having a refractive index higher than the refractive index of the base nanoimprint film.

[0090]

[0092] 39. A densified nanoimprint film comprising: a base nanoimprint film comprising nanoparticles, the nanoparticles comprising titanium oxide, zirconium oxide, niobium oxide, tantalum oxide, hafnium oxide, chromium oxide, indium tin oxide, silicon nitride, or any combination thereof; and a metal oxide disposed on the base nanoimprint film and between the nanoparticles, the metal oxide comprising aluminum oxide, titanium oxide, zirconium oxide, niobium oxide, tantalum oxide, indium oxide tin oxide, hafnium oxide, chromium oxide, scandium oxide, tin oxide, zinc oxide, yttrium oxide, praseodymium oxide, magnesium oxide, silicon oxide, silicon nitride, silicon oxynitride, or any combination thereof.

[0091]

[0093] 40. The densified nanoimprinted film of paragraph 39, wherein the base nanoimprinted film includes voids disposed between the nanoparticles, and the metal oxide is at least partially disposed within the voids.

[0092]

[0094] 41. The densified nanoimprinted film of paragraph 40, wherein at least 3% of the volume occupied by voids in the base nanoimprinted film contains a metal oxide.

[0093]

[0095] 42. The densified nanoimprinted film of paragraph 41, wherein about 20% to about 90% of the volume occupied by the voids in the base nanoimprinted film contains metal oxide.

[0094]

[0096] 43. The densified nanoimprinted film of any one of paragraphs 39 to 42, wherein the nanoparticles comprise titanium oxide.

[0095]

[0097] 44. The densified nanoimprinted film of paragraph 43, wherein the metal oxide comprises aluminum oxide.

[0096]

[0098] 45. A densified nanoimprinted film according to any one of paragraphs 39 to 44, wherein the base nanoimprinted film is a film produced by an imprinting process including a spin-coating process, and the metal oxide is a coating deposited by an atomic layer deposition process.

[0097]

[0099] 46. ​​The densified nanoimprint film of any one of paragraphs 39 to 45, having a higher hardness, fracture strain, yield strength, and / or etch resistance value than the base nanoimprint film.

[0098]

[0100] 47. A densified nanoimprinted film according to any one of paragraphs 39 to 46, having a lower elastic modulus value than the base nanoimprinted film.

[0099]

[0101] 48. A densified nanoimprint film according to any one of claims 39 to 47, wherein the refractive index of the densified nanoimprint film is from about 0.5% to about 30% higher than the refractive index of the base nanoimprint film.

[0100]

[0102] 49. A method of forming a nanoimprint film, comprising: positioning a substrate including a porous nanoimprint film in a processing chamber, the porous nanoimprint film comprising nanoparticles and voids between the nanoparticles, the nanoparticles comprising titanium oxide, zirconium oxide, niobium oxide, tantalum oxide, hafnium oxide, chromium oxide, indium tin oxide, silicon nitride, or any combination thereof; and depositing a metal oxide on the porous nanoimprint film and within at least a portion of the voids to produce a densified nanoimprint film during an atomic layer deposition (ALD) process, the metal oxide comprising aluminum oxide, titanium oxide, zirconium oxide, niobium oxide, tantalum oxide, indium oxide, indium tin oxide, hafnium oxide, chromium oxide, scandium oxide, tin oxide, zinc oxide, yttrium oxide, praseodymium oxide, magnesium oxide, silicon oxide, silicon nitride, silicon oxynitride, or any combination thereof.

[0101]

[0103] 50. The method of paragraph 49, wherein the ALD process includes sequentially exposing the porous nanoimprinted film to a metal precursor and an oxidant during ALD cycles to deposit a metal oxide.

[0102]

[0104] 51. The method of paragraph 50, wherein the ALD cycle is repeated from 2 to about 50 times during deposition of the metal oxide during the ALD process.

[0103]

[0105] 52. The method of any one of paragraphs 49-51, wherein at least 3% of the volume occupied by the voids is filled with metal oxide by an ALD process.

[0104]

[0106] 53. The method of any one of paragraphs 49-52, wherein about 20% to about 90% of the volume occupied by the voids is filled with metal oxide by an ALD process.

[0105]

[0107] 54. The method of any one of paragraphs 49-53, wherein the densified nanoimprinted film has a higher hardness, fracture strain, yield strength, and / or etch resistance value than the base nanoimprinted film.

[0106]

[0108] 55. The method of any one of paragraphs 49 to 54, wherein the densified nanoimprinted film has a lower modulus value than the base nanoimprinted film.

[0107]

[0109] 56. The method of any one of claims 49-55, wherein the refractive index of the densified nanoimprinted film is about 0.5% to about 30% higher than the refractive index of the base nanoimprinted film.

[0108]

[0110] 57. The method of any one of paragraphs 49-56, wherein a porous nanoimprinted film is formed on the substrate by an imprint process including disposing an imprint composition comprising nanoparticles on the substrate, contacting the imprint composition with a stamp having a pattern, converting the imprint composition into a porous nanoimprinted film, and removing the stamp from the porous nanoimprinted film.

[0109]

[0111] 58. The method of paragraph 57, wherein the imprint composition is converted into a porous nanoimprint film by exposing the imprint composition to heat, ultraviolet light, infrared light, visible light, microwave radiation, or any combination thereof.

[0110]

[0112] 59. The method of paragraph 57, wherein converting the imprint composition into a porous nanoimprint film further comprises exposing the imprint composition to a light source having a wavelength of about 300 nm to about 365 nm.

[0111]

[0113] 60. The method of paragraph 57, wherein converting the imprint composition into a porous nanoimprint film further comprises heating the imprint composition to a temperature of about 30° C. to about 100° C. for a period of about 30 seconds to about 1 hour.

[0112]

[0114] 61. The method of paragraph 57, wherein converting the imprint composition into a porous nanoimprint film further comprises heating the imprint composition to a temperature of about 50°C to about 60°C for a period of about 1 minute to about 15 minutes.

[0113]

[0115] 62. The method of paragraph 57, wherein the imprint composition is disposed on the substrate by spin coating, drop casting, or blade coating.

[0114]

[0116] 63. The method of paragraph 57, wherein the imprint composition is disposed on the substrate as a layer having a thickness of about 50 nm to about 1000 nm.

[0115]

[0117] 64. The method of paragraph 57, wherein the imprint composition is disposed on the substrate as a layer having a thickness of about 100 nm to about 400 nm.

[0116]

[0118] 65. The method of paragraph 57, wherein the pattern on the stamp is a one-dimensional pattern, a two-dimensional pattern, or a three-dimensional pattern.

[0117]

[0119] 66. An optical device comprising a grating, the optical device comprising a densified nanoimprinted film according to any one of paragraphs 39 to 48.

[0118]

[0120] 67. An optical device with a grating, comprising a densified nanoimprinted film produced by the method of any one of paragraphs 49-65.

[0119]

[0121] 68. An optical device with a grating comprising a densified nanoimprinted film, the densified nanoimprinted film comprising: a base nanoimprinted film comprising nanoparticles, the nanoparticles comprising titanium oxide, zirconium oxide, niobium oxide, tantalum oxide, hafnium oxide, chromium oxide, indium tin oxide, silicon nitride, or any combination thereof; and a metal oxide disposed on the base nanoimprinted film and between the nanoparticles, the metal oxide comprising aluminum oxide, titanium oxide, zirconium oxide, niobium oxide, tantalum oxide, indium oxide tin oxide, hafnium oxide, chromium oxide, scandium oxide, tin oxide, zinc oxide, yttrium oxide, praseodymium oxide, magnesium oxide, silicon oxide, silicon nitride, silicon oxynitride, or any combination thereof.

[0120]

[0122] While the above description is directed to embodiments of the present disclosure, other and further embodiments may be devised without departing from the basic scope of the present disclosure, the scope of which is determined by the claims. All documents described herein are incorporated by reference, including any priority documents and / or test procedures, to the extent not inconsistent with the body of this specification. As is apparent from the summary and specific embodiments set forth above, while forms of the present disclosure have been illustrated and described, various modifications can be made without departing from the spirit and scope of the present disclosure. Thus, it is not intended that the present disclosure be limited to the forms of the present disclosure as illustrated and described. Similarly, the word "comprising" is considered synonymous with the word "including" as interpreted under US law. Similarly, whenever a composition, element, or group of elements precedes the transitional phrase "comprising," it is understood that the same composition or group of elements is contemplated with the transitional phrase "consisting essentially of," "consisting of," "selected from the group consisting of," or "is," following the recitation of the composition, element, or group, and vice versa.

[0121]

[0123] Certain embodiments and features have been described using a set of upper numerical limits and a set of lower numerical limits. It is to be understood that ranges including any combination of two values ​​are envisioned, for example, any lower value with any upper value, any two lower values, and / or any two upper values, unless otherwise indicated. One or more claims are set forth with specific lower limits, upper limits, and ranges.

Claims

1. A densified nanoimprinted film, a base nanoimprint film comprising nanoparticles, the nanoparticles comprising titanium oxide, zirconium oxide, niobium oxide, tantalum oxide, hafnium oxide, chromium oxide, indium tin oxide, silicon nitride, or any combination thereof; and a metal oxide disposed on the base nanoimprint film and between the nanoparticles, the metal oxide comprising aluminum oxide, titanium oxide, zirconium oxide, niobium oxide, tantalum oxide, indium oxide, indium tin oxide, hafnium oxide, chromium oxide, scandium oxide, tin oxide, zinc oxide, yttrium oxide, praseodymium oxide, magnesium oxide, silicon oxide, silicon nitride, silicon oxynitride, or any combination thereof; A densified nanoimprinted film comprising:

2. 2. The densified nanoimprinted film of claim 1 , wherein the base nanoimprinted film includes voids disposed between the nanoparticles, and the metal oxide is at least partially disposed within the voids.

3. 3. The densified nanoimprint film of claim 2, wherein at least 3% of the volume occupied by the voids in the base nanoimprint film contains the metal oxide.

4. 4. The densified nanoimprint film of claim 3, wherein about 20% to about 90% of the volume occupied by the voids in the base nanoimprint film contains the metal oxide.

5. The densified nanoimprinted film of claim 1 , wherein the nanoparticles comprise titanium oxide.

6. The densified nanoimprint film of claim 5 , wherein the metal oxide comprises aluminum oxide.

7. 10. The densified nanoimprint film of claim 1, wherein the base nanoimprint film is a film by an imprint process including a spin coating process, and the metal oxide is a coating deposited by an atomic layer deposition process.

8. 10. The densified nanoimprint film of claim 1 having higher hardness, fracture strain, yield strength, and / or etch resistance values ​​than the base nanoimprint film.

9. 10. The densified nanoimprint film of claim 1 having a lower modulus value than the base nanoimprint film.

10. 10. The densified nanoimprint film of claim 1, wherein the refractive index of the densified nanoimprint film is about 0.5% to about 30% higher than the refractive index of the base nanoimprint film.

11. 1. A method of forming a nanoimprinted film, comprising: Positioning a substrate including a porous nanoimprinted film in a processing chamber, the porous nanoimprinted film including nanoparticles and voids between the nanoparticles, the nanoparticles including titanium oxide, zirconium oxide, niobium oxide, tantalum oxide, hafnium oxide, chromium oxide, indium tin oxide, silicon nitride, or any combination thereof; and depositing a metal oxide on the porous nanoimprint film and within at least a portion of the voids to produce a densified nanoimprint film during an atomic layer deposition (ALD) process, the metal oxide comprising aluminum oxide, titanium oxide, zirconium oxide, niobium oxide, tantalum oxide, indium oxide, indium tin oxide, hafnium oxide, chromium oxide, scandium oxide, tin oxide, zinc oxide, yttrium oxide, praseodymium oxide, magnesium oxide, silicon oxide, silicon nitride, silicon oxynitride, or any combination thereof. The method includes:

12. 12. The method of claim 11 , wherein the ALD process comprises sequentially exposing the porous nanoimprinted film to a metal precursor and an oxidant during ALD cycles to deposit the metal oxide, and the ALD cycles are repeated from 2 to about 50 times during the deposition of the metal oxide during the ALD process.

13. 12. The method of claim 11, wherein about 20% to about 90% of the volume occupied by the voids is filled with the metal oxide by the ALD process.

14. The method of claim 11 , wherein the densified nanoimprint film has a higher hardness, fracture strain, yield strength, and / or etch resistance value than the base nanoimprint film.

15. The method of claim 11 , wherein the densified nanoimprinted film has a lower modulus value than the base nanoimprinted film.

16. 12. The method of claim 11, wherein the refractive index of the densified nanoimprint film is about 0.5% to about 30% higher than the refractive index of the base nanoimprint film.

17. The porous nanoimprint film is formed on the substrate by an imprint process, the imprint process comprising: disposing an imprint composition comprising the nanoparticles onto the substrate; contacting the imprint composition with a stamp having a pattern; Converting the imprint composition into a porous nanoimprint film; and Removing the stamp from the porous nanoimprinted film. The method of claim 11 , comprising:

18. 20. The method of claim 17, wherein converting the imprint composition to the porous nanoimprint film further comprises exposing the imprint composition to a light source having a wavelength of about 300 nm to about 365 nm.

19. 20. The method of claim 17, wherein converting the imprint composition into the porous nanoimprint film further comprises heating the imprint composition to a temperature of about 30° C. to about 100° C. for a period of about 30 seconds to about 1 hour.

20. An optical device with a grating, comprising a densified nanoimprinted film, The densified nanoimprint film is a base nanoimprint film comprising nanoparticles, the nanoparticles comprising titanium oxide, zirconium oxide, niobium oxide, tantalum oxide, hafnium oxide, chromium oxide, indium tin oxide, silicon nitride, or any combination thereof; and a metal oxide disposed on the base nanoimprint film and between the nanoparticles, the metal oxide comprising aluminum oxide, titanium oxide, zirconium oxide, niobium oxide, tantalum oxide, indium oxide, indium tin oxide, hafnium oxide, chromium oxide, scandium oxide, tin oxide, zinc oxide, yttrium oxide, praseodymium oxide, magnesium oxide, silicon oxide, silicon nitride, silicon oxynitride, or any combination thereof; An optical device comprising a grating.

Citation Information

Patent Citations

  • Thin film solar cell

    JP2012174735A

  • Light extraction film for organic light-emitting diode display device

    JP2015158690A

  • Photocurable resin composition and highly refractive resin cured body

    JP2019123881A

  • Patterned nanoparticle structures

    US20140072720A1

  • Method for manufacturing module having plurality of pattern regions, module having plurality of pattern regions and manufactured according to method, and method for manufacturing diffraction grating module or mold for diffraction grating module

    WO2019035579A1